A Practical Implementation of Brackish Water Treatment with Local Material in Sidoarjo Regency, East Java, Indonesia - Surya Hermawan; Felix Apriyanto; Ivan Reynaldi Limantara; Daniel Steven; Jason Fernaldi; Jescey Edlin Prajogo (Institute of Research and Community Outreach - Petra Christian University, 2023)
Indonesia, an archipelago with vast coastal areas consisting of 809 coastal villages, still faces the same problems of clean water scarcity and accessibility. This research goals are to discover appropriate inexpensive local filtering media and lower the salinity of brackish water in Sidoarjo Regency Indonesia. Regarding previous invention and research, this study deploy an experimental method by physical experiment including local materials along with chemical experiment: ion exchangers as well as reverse osmosis (RO). The outcomes demonstrate that local media filtration utilizing a combination of a 10-micron filter, kaolin, zeolite, kaolin, activated carbon, and kaolin is the best combination to produce the most transparent, and odorless water. It can reduce Total Dissolved Solid (TDS) and Electrical Conductivity (EC) values by 8.59% and 7.18%, and reduce pH levels by 2.59%. On the other hand, reverse osmosis and ion exchange can achieve 99.5% and 67% reductions in TDS and EC values, respectively.